Formation of glutathionyl dinitrosyl iron complexes protects against iron genotoxicity1. Issue 28 (28th July 2015) - Lewandowska, Hanna; Sadło, Jarosław; Męczyńska, Sylwia; Stępkowski, Tomasz M.; Wójciuk, Grzegorz; Kruszewski, Marcin
<x xml:space="preserve">Abstract</x> Formation of glutathionyl nitrosyl complexes abolishes the in vitro genotoxic effect of iron ions alone and iron ions in the presence of a naturally abundant antioxidant, GSH.